2011
DOI: 10.1080/00223980.2011.574168
|View full text |Cite
|
Sign up to set email alerts
|

A Multilevel Study on the Relationships Between Work Characteristics, Self- Efficacy, Collective Efficacy, and Organizational Citizenship Behavior: The Case of Taiwanese Police Duty-Executing Organizations

Abstract: Public security, traffic management, and service for the people are the 3 major functions of policing in Taiwan. This definition encompasses not only the traditional job characteristics, but also the level of contextual characteristics and social characteristics because of police work's characteristics and its frequent interaction with the public. Thus, the present study conducted a multilevel model analysis by taking self-efficacy and collective efficacy as the mediating variables. The purpose was to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 44 publications
1
38
0
3
Order By: Relevance
“…These studies indicated that people with high self-effi cacy express loyalty to the workplace and are more willing to take part in extra-role tasks ( Todd & Kent, 2006 ;Chen & Kao, 2011 ;Beauregard, 2012 ).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…These studies indicated that people with high self-effi cacy express loyalty to the workplace and are more willing to take part in extra-role tasks ( Todd & Kent, 2006 ;Chen & Kao, 2011 ;Beauregard, 2012 ).…”
Section: Discussionmentioning
confidence: 97%
“…The lack of interaction between job self-effi cacy and caregiving hyperactivation indicates that the latter is expressed under both conditions of job self-effi cacy. Future studies may investigate whether personal resources (such as emotional, material, or motivational) or work characteristics (Chen & Kao, 2011) moderate the associations between hyperactivation and OCB.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Gazetted police officers were chosen because they are more likely to engage in organisational citizenship behaviour than non-gazetted police officers (Chen & Kao 2011). The questionnaires were distributed in Klang valley, Malaysia because of the concentration of gazetted police officers in the area which accounted for sixty percent of the total gazetted police force in Malaysia.…”
Section: Methodsmentioning
confidence: 99%